2019
DOI: 10.1002/wer.1094
|View full text |Cite
|
Sign up to set email alerts
|

Modified anaerobic digestion model No.1 (ADM1) for modeling anaerobic digestion process at different ammonium concentrations

Abstract: Anaerobic digestion (AD) is an established method for sustainable energy production. Anaerobic digestion model No.1 (ADM1) was used to simulate methane production (MP) and volatile fatty acid (VFA) concentrations at different ammonium concentrations. In accordance with the incomplete description of several biochemical reactions and the omission of several reaction processes, ADM1 was modified with the consideration of acetic acid inhibition and valeric acid existence. ADM1_ac (ADM1 added acetic acid inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…These high TVFA values may be related to the inhibition of acetoclastic methanogenesis [42]. Li, X. et al [43] reported that in the AD process, valeric acid is not normally generated in appreciable amounts and that the formation of this VFA is due to the reversibility of the biochemical reactions of acetic acid, propionic acid, and hydrogen.…”
Section: Ph and Total Acidity (Tvfa) In Anaerobic Co-digestion Of Exhausted Sugar Beet Pulp And Cattle Manurementioning
confidence: 99%
“…These high TVFA values may be related to the inhibition of acetoclastic methanogenesis [42]. Li, X. et al [43] reported that in the AD process, valeric acid is not normally generated in appreciable amounts and that the formation of this VFA is due to the reversibility of the biochemical reactions of acetic acid, propionic acid, and hydrogen.…”
Section: Ph and Total Acidity (Tvfa) In Anaerobic Co-digestion Of Exhausted Sugar Beet Pulp And Cattle Manurementioning
confidence: 99%
“…As noted earlier, the model is far from perfect but its flexibility and structure means it is suitable as a tool to be used at the design stage of AD plant development, for qualitative scenario testing, or for benchmarking control schemes [63][64][65]. As with the ASMs, modifications to the model have been implemented based on process requirements, such as operating mode [66,67], or to include new biochemical processes [68,69]. A more comprehensive transition to a consensus ADM No.…”
Section: A First-principles Engineering Approach To Modelling Anaerobic Digestionmentioning
confidence: 99%
“…Such a multi-scale model is highly complex and requires a large degree of multi-disciplinarity to ensure successful implementation. However, the use of IbMs is becoming more ubiquitous and recent efforts to develop large scale simulators of EBS using hybrid IbM and statistical emulators have established a framework for studying microbial community behaviour at scale [69,173,174], opening the door for application to anaerobic digestion processes [172,175] (See Fig. 5 for an example application of an IbM applied to anaerobic processes).…”
Section: Individual-based Modellingmentioning
confidence: 99%
“…The two-phase (solid, liquid) model simulated the increasing diameter granular biomass using a multilayer biofilm model. Using laboratory-scale thermophilic glucose digestion data for model verification, the ADM1 digestion model was extended to incorporate the valeric acid dynamics and acetic acid inhibition (Li, Yang, Liu, Ma, & Wang, 2019). Miletic, Rieger, Schraa, and Wade (2019) presented the concept of a statistical partial least squares model for predicting the wastewater orthophosphate concentration based on its multivariate correlation with the wastewater concentrations of chemical oxygen demand (COD), TSS, ammonia, pH, dissolved oxygen (DO), and temperature.…”
Section: Modelingmentioning
confidence: 99%
“…The two‐phase (solid, liquid) model simulated the increasing diameter granular biomass using a multilayer biofilm model. Using laboratory‐scale thermophilic glucose digestion data for model verification, the ADM1 digestion model was extended to incorporate the valeric acid dynamics and acetic acid inhibition (Li, Yang, Liu, Ma, & Wang, 2019).…”
Section: Modelingmentioning
confidence: 99%